Corrosion Measurements in Reinforced Fly Ash Concrete Containing Steel Fibres Using Strain Gauge Technique. (25th November 2013) - Sounthararajan, V. M.; Sivakumar, A.
Abstract : Corrosion of steel bars in concrete is a serious problem leading to phenomenal volume expansion and thereby leading to cover concrete spalling. It is well known that the reinforced concrete structures subjected to chloride attack during its service life cause these detrimental effects. The early detection of this damage potential can extend the service life of concrete. This study reports the comprehensive experimental studies conducted on the identification of corrosion mechanism in different types of reinforced concrete containing class-F fly ash and hooked steel fibres. Fly ash replaced concrete mixes were prepared with 25% and 50% fly ash containing steel fibres at 0.5%, 1.0%, and 1.5% by volume fraction. Corrosion process was investigated in an embedded steel bar (8 mm diameter) reinforced in concrete by passing an impressed current in sodium chloride solution. Strain gauge attached to the rebars was monitored for electrical measurements using strain conditioner. Strain gauge readings observed during the corrosion process exhibited the volume changes of the reinforcement embedded inside the concrete. The corrosion potential of different steel fibre reinforced concrete mixes with fly ash addition showed higher resistance towards the corrosion initiation.